9514 1404 393
Answer:
x = 6
Explanation:
You want x on one side of the equation and a constant on the other side. Subtract the terms you don't want where they are.
Here, the smaller x-term is on the right, so we can subtract that to put all the x-terms on the left. The left side has a constant of 3 that we will not want there with the x-terms. So, we can subtract 2x+3 from both sides to get ...
3 +6x -(2x +3) = 2x +27 -(2x +3)
4x = 24 . . . . . . simplify
x = 24/4 . . . . divide by the coefficient of x
x = 6